A CLINICAL STUDY ON THE EFFICACY OF TIMIRHAR LAUHA AND BALADI GHRIT TARPANA IN THE MANAGEMENT OF TIMIRA WITH SPECIAL REFERENCE TO MYOPIA (AYUSHDHARA, 2020)
Myopia is a refractive error which affects every age group person around the world. Specially in modern age when the use of mobile screen and computer is increased so much, this error has become horrible. The symptoms of myopia closely resembles with the disease Timir. It involves pratham and dwitiya patala of Netra. In the present study, 35 clinically diagnosed patients of Timira/Myopia were selected and randomly divided into two groups (Group-A-18 patients, Group-B-17patients) out of these, 30 patients completed the trial. Patients of group A were administrated Timirhar Lauha orally. While patients of group B were topically administrated Baladi Ghrita for Tarpana and Timirhar Lauha orally. The study shows that Timirhar Lauha (systemic drug) alone was effective in all symptoms of Timira /Simple Myopia but combination of the drug Timirhar Lauha (systemic drug) with Baladi Ghrita (Tarpana/topical application) had much greater potential to ameliorate the symptoms of Timira /Simple Myopia.